Um estudo sôbre educação em saúde nas escolas das Filipinas Health education in the Schools of the Philippines - Ruth Sandoval Marcondes (Universidade de São Paulo, 1971)
Descrevem-se alguns aspectos do programa de educação em saúde nas escolas das Filipinas. O programa abrange quatro dimensões: ambiente físico e emocional da escola, serviços de saúde, ensino da saúde e relações lar-escola-comunidade. Treinamento de pessoal para educação em saúde na escola é especialmente focalizado. Some aspects of the school health education program in the Republic of the Philippines are described. The program is four-dimentional: physical and emotional environment, health services, health teaching and school-home-community relationships. Personnel training for school health education is particularly focused.